Adaptive Bandwidth Allocation in Network Function Virtualization: A Multi-Tenant Optimization Method Using Artificial Intelligence - Ling, Prof. Mei (American Journal of Data Science and Artificial Intelligence Innovations, 2022)
NFV scales and facilitates flexible deployment of telecom network services. Changing traffic, demands, and resource allocation challenges multi-tenant NFV bandwidth management. Optimizing NFV AI bandwidth. Particularly machine learning techniques, artificial intelligence might improve real-time NFV performance, user experiences, and resource economy. AI handles multi-tenant systems, anticipates bandwidth, and best allocates resources. Evaluating artificial intelligence-managed NFV opportunities, drawbacks, and performance.